Neural Networks - Jordan, M. I.; Bishop, Christopher (Tucker, A. B. (Ed.), The Computer Science and Engineering Handbook, 1997)
VC dimension: A measure of the complexity of a model. Knowledge of the VC dimension permits an estimate to be made of the difference between performance on the training set and performance on the test set.